The Influence of Character Education and Learning Motivation on Competence and Performance of Indonesian Navy PUSDIKLEK Graduates - Nordi Dwi Purwanto; Hanjar K Hanjar; Achmad Faisol (International Journal of Enterprise Modelling, 2026)
This study addresses the need to enhance the competence and performance of graduates from the Indonesian Navy’s Education and Training Center (Pusdiklek), particularly in response to evolving technological and operational demands that reveal gaps in current training outcomes. The study aims to analyze the direct and indirect effects of character education and learning motivation on competence and performance, with competence acting as a mediating variable. A quantitative approach was employed using Structural Equation Modeling (SEM) with a sample of 164 respondents selected through simple random sampling from a population of 277 personnel. Data were collected באמצעות a structured questionnaire using a 5-point Likert scale and analyzed using AMOS 24. The results indicate that character education significantly influences competence (β = 0.415; p < 0.001) and performance (β = 0.288; p < 0.001), while learning motivation has a stronger effect on competence (β = 0.522; p < 0.001) and performance (β = 0.454; p < 0.001). Competence also significantly affects performance (β = 0.359; p < 0.001) and mediates the relationship between character education (β = 0.149; p = 0.003) and learning motivation (β = 0.187; p = 0.002) on performance. These findings confirm a partial mediation model and highlight the importance of integrating character development and motivational strategies in military training systems. The study contributes theoretically by developing an integrated SEM-based framework in a military education context and practically by providing strategic insights for improving training effectiveness and personnel performance in the Indonesian Navy.